Reforestation amidst deforestation in the Bayano-Darién frontier, Eastern Panama: variations on the forest- transition thesis (2022)
eng: The literature on tropical forest-cover change observes a set of drivers responsible for transitions toward reforestation – the so-called 'forest transition'. Uncertainty still exists over how the drivers behave in the transition and how trends in reforestation manifest in different contexts. Focusing on the Panamanian agricultural frontier of the Bayano-Darién, this thesis combines household surveys, remote sensing / GIS analysis and participant observation to describe nascent trends in reforestation for key actors and scales, and in relation to antecedent patterns pattern of land-cover change. Results indicate that the forest-transition is aligned with the patterns of previous land-cover change. In Eastern Panama, reforestation appears as a fringe event in the landscape. Though reforestation is popular with some large-scale actors, smallholders continue to convert forest to pasture, resulting in net deforestation.